Respuesta :
Answer:
f+g = 11x-8
f*g = 28x^2 - 47x+15
Step-by-step explanation:
f(x) = 4x - 5 and g(x) = 7x -3
(f+g)(x) = 4x - 5 + 7x -3
Combine like terms
= 4x+7x -5-3
= 11x-8
(f * g) (x) = ( 4x - 5) (7x -3)
FOIL
= 4x*7x + 4x(-3) + (-5)(7x) + (-5)(-3)
=28x^2 -12x-35x+15
Combine like terms
=28x^2 - 47x+15
Step-by-step explanation:
Step 1: Find (f + g)(x)
The definition of (f + g)(x) is f(x) + g(x). Basically add the two functions together.
[tex]f(x) + g(x)[/tex]
[tex](4x - 5) + (7x - 3)[/tex]
[tex]11x - 8[/tex]
Answer: [tex]11x - 8[/tex]
Step 2: Find (f * g)(x)
The definition of (f * g)(x) is f(x) * g(x). Basically multiply the two functions together.
[tex]f(x) * g(x)[/tex]
[tex](4x - 5) * (7x - 3)[/tex]
[tex](4x * 7x) + (4x * -3) + (-5 * 7x) + (-5 * -3)[/tex]
[tex](28x^{2}) + (-12x) + (-35x) + (15)[/tex]
[tex]28x^{2} - 47x + 15[/tex]
Answer: [tex]28x^{2} - 47x + 15[/tex]